Association between physical activity and sleep quality among healthcare students - Alhusami, MinatAllah; Jatan, Noora; Dsouza, Skylar; Sultan, Meshal A. (Frontiers in Sports and Active Living, 2024)
Objective To assess the relationship between physical activity (PA) and sleep quality (SQ) in Mohammed Bin Rashid University (MBRU) students in Dubai, United Arab Emirates. Taking into account this being one of the first studies exploring this aspect among healthcare students in the Gulf Cooperation Council (GCC) countries. Methods This is an analytical cross-sectional study that involved disseminating online surveys via email to students of all 5 colleges in MBRU between March-June 2023. The survey encompassed queries on demographics, the Saltin-Grimby Physical Activity Level Scale (SGPALS), the International Physical Activity Questionnaire-Short Form (IPAQ-SF), and the Pittsburgh Sleep Quality Index (PSQI). Results The survey was completed by 105 students. Most students were from the medical college (98/105; 93.3%) and were females (84/105; 80.0%). Females engaged the most in low PA (44.0%) while males engaged the most in high PA (42.9%) according to the IPAQ-SF. There was a significant association between SGPALS and gender (p = 0.007, X2 = 12.0). The global PSQI score showed that 70.5% of the students had bad-quality sleep. Sleep efficiency and leisurely PA are significantly negatively correlated (p = 0.026, ρ = −0.217) while sitting minutes and sleep duration are significantly positively correlated (p = 0.030, r = 0.212). Conclusion Significant negative correlations between sleep efficiency and leisurely PA demonstrate that while exercise has been implicated in the improvement of SQ, excessive exercise can behave as an additional stressor and induce negative changes in the SQ of healthcare students. Meanwhile, significant positive correlations between sleep duration and sitting indicate that adequate rest should not be undervalued in its effects on sleep. Furthermore, the findings of this study highlight public health implications that warrant attention by educators and policymakers in academic health systems.